2012
DOI: 10.1177/0091270011407916
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Quality of Publications on Randomized Clinical Trials Using the Consolidated Standards of Reporting Trials (CONSORT) Statement Guidelines in a Spanish Tertiary Hospital

Abstract: The main reason for conducting a clinical trial (CT) is to test the effect of a drug or medical procedure to improve treatment of a disease. CTs contribute most when they are rigorously conducted and the results are published adequately. The aim of this study is to assess, using the CONSORT statement guidelines, the quality of reporting of completed CTs conducted at a tertiary hospital to determine which sections of the articles should be improved. CTs published between 2002 and 2008 were identified by searchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…Firstly, CONSORT is officially supported by the World Association of Medical Authors and the International Committee of Medical Journal Editors. Secondly, several reports demonstrated that the quality of reporting could be improved if the CONSORT statement was followed more closely[37]–[40]. Thirdly, CONSORT has been applied in many other medical specialities[41][43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, CONSORT is officially supported by the World Association of Medical Authors and the International Committee of Medical Journal Editors. Secondly, several reports demonstrated that the quality of reporting could be improved if the CONSORT statement was followed more closely[37]–[40]. Thirdly, CONSORT has been applied in many other medical specialities[41][43].…”
Section: Discussionmentioning
confidence: 99%
“…Francisco Dasí et al concluded that “even high-impact journals publish articles of unsuitable quality” [40].…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome measure was the FMA-UE, a reliable and validated 66-points outcome measure quantifying arm motor function after stroke [25]. Other clinical outcome measures were: FMA for sensory function (FMA-sensation); Box and Blocks Test (BBT) for gross manual dexterity [26]; Modified Ashworth Scale (MAS) for measuring muscle tone at biceps brachii [27]; Functional Independence Measure ( FIM) for autonomy in ADLs [28].…”
Section: Clinical Data Assessment and Outcome Measurementioning
confidence: 99%
“…Have these guidelines had sufficient impact on the reporting and the accessibility of research to the wider public, as well as clinicians and researchers? It appears that the answer to this is no, at least not in psychiatry 8,9 nor for pharmacological 10 and nonpharmacological trials in general, 11 for trials of treatments for cancer 12 nor for some trials in anaesthetics. 13 Psychiatric studies are especially challenging as the trials can include pharmacological and non-pharmacological interventions, devices, surgery, psychological treatments, complex multi-component interventions in hospital or community settings, public health and policy interventions in single or cluster randomised designs, and more.…”
Section: Time Tenacity and Trials: Improving The Quality Of Researchmentioning
confidence: 99%